Heritability estimates for gonadal development traits and their genetic correlations with growth and heat tolerance traits in the Fujian Oyster Crassostrea angulata - Han, Ziqiang; Guo, Xiang; Lu, Zuoliang; Song, Yiheng; Chen, Ruimin; Han, Xiaojie; Yu, Shiqi; Tu, Kang; Liu, Liangjie; Que, Huayong (Frontiers in Marine Science, 2022)
Improving the progress of breeding is the main purpose of breeders, and shorting the reproductive cycle is one of the ways to improve the breeding progress. Although the reproductive cycle of Crassostrea angulata can be shortened from one year to half a year by selecting precocious individuals, little is known about whether this selection will accelerate their gonadal development or disturb their selection for productive traits. Here, the heritability of gonadal development traits (gametogenic stage and egg diameter) and their genetic correlations with both growth traits (shell height at 4 and 12 months and total body weight at 12 months) and heat tolerance trait were estimated. The heritability for gametogenic stage was low (0.18 ± 0.09), while the egg diameter showed a high heritability (0.78 ± 0.30). These results suggest that selection for precocious individuals has little effect on the rate of gonadal development in the C. angulata, despite the effect may be greater in females than in males. The genetic correlations between gonadal development traits and both growth (-0.02–0.30) and heat tolerance traits (-0.08–0.34) were low and non-significant. These results suggest that selection for precocious individuals has negligible effects on their productive traits. Therefore, it is feasible to double the breeding efficiency of C. angulata by halving their reproductive cycle.